2014
DOI: 10.4062/biomolther.2014.054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Radiation Exposure on Stress-Related Behaviors and Stress Hormones in Male Wistar Rats

Abstract: Studies have demonstrated that electromagnetic waves, as the one of the most important physical factors, may alter cognitive and non-cognitive behaviors, depending on the frequency and energy. Moreover, non-ionizing radiation of low energy waves e.g. very low frequency waves could alter this phenomenon via alterations in neurotransmitters and neurohormones. In this study, short, medium, and long-term exposure to the extremely low frequency electromagnetic field (ELF-EMF) (1 and 5 Hz radiation) on behavioral, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…These changes could be due to the food intake or catabolic action changes. In a previous study, we were evaluated 1 and 5 Hz ELF-EMF radiation affects on behavioral, hormonal, and metabolic of rats (Mahdavi et al, 2014). Results indicated that weight of irradiated rats did not change, and also no alter was observed in food and water intakes of rats after exposure to EMF-ELF in comparison to the control group.…”
Section: Discussionmentioning
confidence: 90%
“…These changes could be due to the food intake or catabolic action changes. In a previous study, we were evaluated 1 and 5 Hz ELF-EMF radiation affects on behavioral, hormonal, and metabolic of rats (Mahdavi et al, 2014). Results indicated that weight of irradiated rats did not change, and also no alter was observed in food and water intakes of rats after exposure to EMF-ELF in comparison to the control group.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies have examined ULF radiation prior to earthquakes [7,8,47], and some studies reported the leading times were between a few weeks and a month [4,48]. Some reports suggest that the ULF magnetic field affects behavior and hormones [49,50,51,52,53]. The electromagnetic field with a frequency of 10 Hz is known to affect circadian activity rhythms [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The electromagnetic field with a frequency of 10 Hz is known to affect circadian activity rhythms [52,53]. Mahdavi et al [49,51] have reported that exposures to electromagnetic fields with 5 Hz or 12 Hz elevated activity levels and adrenocorticotropic hormone concentrations in rats. Additionally, there have been reports that cattle aligned their body axes along geomagnetic field lines, which indicates they have the sense of magnetoreception [54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats showed decrease in learning, memory processes, and anorexia cases under a certain frequency of EMF (Mahdavi, 2014). On the other hand, Ghrelin`s concentration must be increased in case of anorexia and is used in stimulating the learning processes.…”
Section: Introductionmentioning
confidence: 99%